PENGEMBANGAN SEKTOR PERIKANAN DAN KELAUTAN DI KABUPATEN NIAS UTARA - Munthe, Mario Nicolas (UNIKA Santo Thomas, 2019)
This research aims to determine the strategy for developing the fisheries and marine sector in North Nias Regency. The population in the study was all fishermen in North Nias District until 2018 with a total population of 2,276 fishermen. The sampling method is purposive sampling method. With the purposive sampling method, a sample of 90 fishermen was obtained. The analytical method used is the SWOT analysis. From the results of the analysis it was found that for freshwater fisheries an aggressive growth strategy by increasing the production capacity of freshwater aquaculture by using the strength of potential land area and sufficient water discharge and for capture fisheries with the development of capture fisheries with the addition of fishing fleets, development of processing catches and increased investment from outside to increase small-scale fisheries.